Doubly Cavitand‐Capped Zn‐Porphyrin Capsule with Simultaneous Encapsulation of Guest and Ligand, and Its Application to Doubly Cavitand‐Capped Double‐Decker Zn‐Porphyrin Capsule. Issue 2 (16th December 2021) - Nakabayashi, Kakeru; Kishimoto, Kazuki; Kobayashi, Kenji
Abstract: A 1 : 2 mixture of Zn‐ meso ‐tetrakis(4‐dodecyl‐3, 5‐dihydroxyphenyl)porphyrin (1‐Zn ) and tetrakis(4‐pyridylethynyl)cavitand (2 ) in C6 D6 self‐assembles quantitatively into the doubly cavitand‐capped Zn‐porphyrin capsule 2 ⋅ 1‐Zn ⋅ 2 with two cavities divided by the porphyrin ring via eight ArOH⋅⋅⋅Npy hydrogen bonds. Simultaneous encapsulation of 1‐acetoxy‐3, 5‐dimethoxybenzene (G ) and 4‐(4‐methylphenyl)pyridine (L2 ) in 2 ⋅ 1‐Zn ⋅ 2 preferentially occurs to form G /L2 @(2 ⋅ 1‐Zn ⋅ 2 ). A 1 : 1 mixture of 1‐Zn and 2 in the presence of G and L2 self‐assembles into the G ‐encapsulating half‐capsule G @(2 ⋅ 1‐Zn ) ⋅ L2 with coordination of L2 at the outer side of 2 ⋅ 1‐Zn . A 2 : 2 : 1 mixture of 1‐Zn, 2, and 1, 4‐diazabicyclo[2.2.2]octane (L3 ) in the presence of G self‐assembles preferentially into the G ‐encapsulating doubly cavitand‐capped double‐decker Zn‐porphyrin capsule G /G @(2 ⋅ 1‐Zn ⋅ L3 ⋅ 1‐Zn ⋅ 2 ) with coordination of L3 between two hydrogen‐bonded 1‐Zn subunits. Thus, selective formation of these cavitand–porphyrin capsules can be controlled by the stoichiometry of 1‐Zn and 2 as well as the character of N‐ligands. Abstract : Selective formation of cavitand‐capped Zn‐porphyrin‐sandwich capsules such as G /L2 @(2 ⋅ 1‐Zn ⋅ 2 ) and G /G @(2 ⋅ 1‐Zn ⋅ L3 ⋅ 1‐Zn ⋅ 2 ) can be controlled by the stoichiometry of porphyrin 1‐Zn and cavitand 2 as well as the character of N‐ligands L2 and L3 in the presence of guest G .